Steam Computing Analysis and Application on Operator Real-time Signal Big Data Processing - Bin Dong; Di Yang; Zheng Wang; Wenhong Zhou (Dianxin kexue)
Big data platform based on the Hadoop structures using offline batch processing mode，unable to meet the service requirements for data timeliness.In order to solve the real-time signal processing requirements in operator OIDD（open information of dynamic data）big data platform，the big-data system components of stream computing were discussed，real-time data collecting，distribution and processing components which formed the end-to-end real-time signal processing big data technology solutions were recommended，and the solutions of the OIDD big data platform which integrated batch computing and stream computing were proposed.It will improve the timeliness of the network signaling data and provide more space for business innovation and bring more benefits.